Lorcaserin requires preproglucagon neurons to reduce food intake in mice and acts additively to liraglutide-induced hypophagia - Ertugrul, N. U.; Yardimci, A.; Ozdede, M. R.; Ozgen, A.; Ozbeg, G.; Canpolat, S. (Wiley, 2022)
[Abstract Not Available]